2007
DOI: 10.1038/sj.ijo.0803774
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness in childhood and adolescence: a powerful marker of health

Abstract: This review aims to summarize the latest developments with regard to physical fitness and several health outcomes in young people. The literature reviewed suggests that (1) cardiorespiratory fitness levels are associated with total and abdominal adiposity; (2) both cardiorespiratory and muscular fitness are shown to be associated with established and emerging cardiovascular disease risk factors; (3) improvements in muscular fitness and speed/agility, rather than cardiorespiratory fitness, seem to have a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

56
1,957
8
208

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,121 publications
(2,363 citation statements)
references
References 105 publications
56
1,957
8
208
Order By: Relevance
“…Low handgrip strength is associated with a greater metabolic risk score in adolescents, 2,26 and poorer handgrip strength is reported in lower SES groups of Spanish 5,27 and Brazilian 10 descent. In Bogotá, we found that handgrip was greater in youth in the mid-and high-SES groups when estimates were adjusted fully.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Low handgrip strength is associated with a greater metabolic risk score in adolescents, 2,26 and poorer handgrip strength is reported in lower SES groups of Spanish 5,27 and Brazilian 10 descent. In Bogotá, we found that handgrip was greater in youth in the mid-and high-SES groups when estimates were adjusted fully.…”
Section: Discussionmentioning
confidence: 96%
“…Cardiorespiratory fitness was assessed with the 20-m shuttlerun test as described by Ortega et al 2 Participants ran between 2 lines 20 m apart in time with prerecorded signals. The initial speed of 8.5 km•h −1 increased by 0.5 km•h −1 each minute, and the test was terminated when participants failed to reach the end lines (keep pace) on 2 consecutive occasions or when the subject stopped due to volitional fatigue.…”
Section: Physical Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we were able to examine the association of breakfast consumption with physical activity and sedentary time using two different methods of measuring these variables. A higher physical activity level has been associated with higher physical fitness, which is a health marker in children and adolescents (10,11) . Thus, to study if breakfast consumption is associated with a health marker in young people is of public health interest.…”
mentioning
confidence: 99%
“…La condición física incluye múltiples dimensiones y componentes, como la aptitud cardiorrespiratoria y la fuerza muscular, las cuales se consideran indicadores muy claros de la salud de niños y adolescentes (13). Una mala condición física suele tener, entre otras consecuencias, la aparición de sobrepeso en niños y jóvenes como resultado de un aumento en el uso de las tecnologías que potencian el sedentarismo, la falta de ejercicio y la disminución de la calidad del sueño (14,15).…”
unclassified